GESTION ENDOGENE DE LA FERTILITE DES TERRES AGRICOLES CHEZ LES LOKPA A BOUGOU (COMMUNE DE DJOUGOU AU NORD- BENIN). - TOHOZIN, ANTOINE YVES; Tondro Mamam, Abdou-Madjidou; FANGNON, BERNARD; Guedenon, D. Janvier; GIBIGAYE, Moussa (My University, 2020)
Agricultural land is becoming increasingly degraded by human pressure for the satisfaction of vital needs. The objective of this research is to study the management of agricultural land fertility among Lokpa in Bougou. Data collection from the field was done on three of the four villages in the Bougou district. The size of the sample is determined by the D. Schwartz formula (1995) with a random sampling mode. In total, 100 people were surveyed. Data collection was conducted through direct field interviews and observation. Allan's L coefficient (1995) has been used to characterize the level of soil disturbance. The Chi-square correlation test was applied using SPSS descriptive statistics software (version 21). The analysis of the results shows that cropping techniques are an important factor in the destruction of agricultural land (71%). Populations still have acquired or endogenous knowledge to assess the level of soil fertility. At the Lokpa in Bougou, the drop in yields agricultural is a main indicator of the appreciation of soil fertility. The Allan L coefficient (1995) calculated is L = 1.2 <5, which explains an overexploitation of farmland. The contribution of chemical fertilizers is highly developed to restore soil fertility. In contrast, less than 5% of farmers believe that soil fertility needs to be restored from organic fertilizer. The value of the threshold of significance between knowledge of soil fertility restoration practices and sex is 0.033 so there is a link between the sex of the farmer and his knowledge of soil fertility restoration practices.
Keywords: Lokpa; Bougou; agricultural land; management modes.